The relationship between physical education teachers' competence support and middle school students' participation in sports: A chain mediation model of perceived competence and exercise persistence. - Yubo Liu; Jianhua Yan; Jing Li (PLoS ONE)
This study explores the relationship between physical education teachers' support and middle school students' participation in sports. It also clarifies this relationship's mediating roles of perceived competence and exercise persistence. A questionnaire survey involved 879 Chinese middle school students, consisting of 434 males and 445 females. The results indicate a significant positive correlation between teachers' competence support and students' participation in sports (p < 0.01). Perceived competence and exercise persistence as important mediators between teachers' competence support and students' involvement in sports, with the mediation effect comprising independent mediation by perceived competence and exercise persistence and a chain mediation effect involving both. The effect value was 0.156, with contributions of 60.4%, 43.6%, and 73.1% to the total mediating effect, respectively. In physical education courses, teachers should enhance their competence to support students, increase students' interest in learning, and promote the development of sports participation. By understanding the predictive roles of teacher support, perceived competence, and exercise persistence on sports participation, strategies can be developed to better enhance students' levels of participation in physical activities, thereby improving their beliefs about physical health and their confidence in exercising.